(untitled) (Research, Society and Development, 2025)
Objective: This study aims to analyze nurses’ knowledge regarding the applicability of the birth plan through an integrative literature review. Methodology: The guiding question was developed using the PICO strategy, defined as: "What is nurses’ knowledge about the creation and applicability of the birth plan?" The search was conducted in 2024 across the SciELO, LILACS, PUBMED, and BDENF databases, considering the period from 2014 to 2024, with no language restrictions. Results: The results showed that nurses have limited knowledge about the birth plan, particularly in its practical application during prenatal care. The need for professional training and the development of protocols to support the implementation of the birth plan as a tool for humanized care was evident. Among the main challenges identified were lack of technical preparation, insufficient ongoing educational initiatives, and the absence of effective integration among levels of healthcare. Final considerations: Data analysis revealed that nurses’ knowledge of the birth plan is limited, which hinders its applicability in prenatal care. The main challenges include a lack of professional training, work overload, and resistance to practices centered on the autonomy of the pregnant woman. Nevertheless, the studies indicate a desire for change, emphasizing the importance of care protocols, continuing education, and academic training focused on the humanization of childbirth.